Pulsed alternating wavelength system lighting does not negatively impact production or welfare but reduces dopamine activity and may improve bone growth in grow-out Pekin ducks - S. Tonissen; B.J. Emmert; J.M. Schober; E.M. Oluwagbenga; D.M. Karcher; G.S. Fraley (Poultry Science)
The production and welfare of Pekin ducks can be affected by the lighting type they are housed under. There is no standard lighting system in industry and little data evaluating effects of different light systems on duck production and welfare. Pulsed Alternating Wavelength System (PAWS) is a novel LED technology that delivers multiple wavelengths of light in pulsating patterns. This study aimed to determine the effects of PAWS on brain serotonin turnover and skeletal quality in ducks. Ducks housed under PAWS were hypothesized to have lower brain serotonin turnover and equal bone quality compared to those housed under control lights (fluorescent with digital ballasts, 4500K, ∼40 lux). Ducks were placed in floor pens under PAWS or control lighting (1200 ducks/pen, n = 4 pens/treatment) at day of hatch until processing at 30 days of age (DOA). Body weights and feed intake were monitored weekly. Brains, femurs, tibiae, and humeri were collected on days 7, 14, 21 and 29 (n = 6 ducks/age/lighting type). Brain serotonin and metabolites were measured. Bone length, width, breaking strength, and ash were determined. Serotonin data were analyzed using 2-way ANOVA for age and lighting treatment with a post-hoc Fisher's LSD test. Bone data were analyzed with independent t-tests between treatments within each age. Ducks housed under PAWS were heavier by 29 DOA than controls (P < 0.001) with no differences in feed conversion. Brain analyses revealed no differences in serotonin turnover between lighting types. Early interstitial growth of PAWS femur and tibia was increased (P < 0.05), and PAWS femurs had increased bone mineral content at 29 DOA (P = 0.001). At 29 DOA, the PAWS humeri were wider than controls (P = 0.025) and had increased geometrical bone mechanical properties (P < 0.003), but no differences in breaking stress were evident. Results suggest that PAWS may have benefits for production traits and skeletal quality, however, a complete understanding of the welfare effects need further study.